LP(a): Structure, Genetics, Associated Cardiovascular Risk, and Emerging Therapeutics - Tasdighi, Erfan; Adhikari, Rishav; Almaadawy, Omar; Leucker, Thorsten M; Blaha, Michael J (Annual review of pharmacology and toxicology, 2024)
Lipoprotein(a) [Lp(a)] is a molecule bound to apolipoprotein(a) with some similarity to low-density lipoprotein cholesterol (LDL-C), which has been found to be a risk factor for cardiovascular disease (CVD). Lp(a) appears to induce inflammation, atherogenesis, and thrombosis. Approximately 20% of the world's population has increased Lp(a) levels, determined predominantly by genetics. Current clinical practices for the management of dyslipidemia are ineffective in lowering Lp(a) levels. Evolving RNA-based therapeutics, such as the antisense oligonucleotide pelacarsen and small interfering RNA olpasiran, have shown promising results in reducing Lp(a) levels. Phase III pivotal cardiovascular outcome trials [Lp(a)HORIZON and OCEAN(a)] are ongoing to evaluate their efficacy in secondary prevention of major cardiovascular events in patients with elevated Lp(a). The future of cardiovascular residual risk reduction may transition to a personalized approach where further lowering of either LDL-C, triglycerides, or Lp(a) is selected after high-intensity statin therapy based on the individual risk profile and preferences of each patient.